Organizational commitment towards turnover intention at MFS Technology (M) Sdn Bhd / Nurul Syafiqah ‘Ulya Hazalan - Hazalan, Nurul Syafiqah ‘Ulya (2011)
This study is designed to study the organizational commitment towards turnover intention at MFS Technology (M) Sdn Bhd. The research used 5 factors in this study which is compensation benefits, communication, job satisfaction, work environment and motivation. In this study, the methods used are questionnaire, interview and observation to identify the relevant information. Researcher also used secondary data such as journals and articles from internet, references books; previous thesis, and report as well as primary data. Researcher also used probability sampling technique which is convenience sampling to gain the information. The results of this study may need MFS changes or improve their quality in order to gain high productivity.